Implementasi Sambang Door to Door Bhabinkamtibmas Dalam Mencegah Tindak Pidana Pencurian : di Wilayah Hukum Polsek Tigaraksa, Tangerang-Banten - Radityatama, Arvin Firdaus; Sumartono, Agus (Prisani Cendekia Institute, 2024)
This study aims to analyze the implementation of the door-to-door visits by Bhabinkamtibmas in the area and the factors influencing this activity. Additionally, it examines the appropriate steps to maximize the effectiveness of the door-to-door visits in preventing theft crimes in the region. This study employs a qualitative research method with a descriptive approach. Data was collected through in-depth interviews with Bhabinkamtibmas personnel, community leaders, and local residents in the jurisdiction of the Tigaraksa Police Sector. Furthermore, direct observation was conducted on the implementation of the door-to-door visits, along with document analysis related to the community security program. The research findings indicate that the implementation of the door-to-door visits by Bhabinkamtibmas has had a positive impact in reducing theft crimes. This initiative has increased public awareness of the importance of neighborhood security, fostered a stronger collaboration between the police and the community in maintaining public order, and facilitated early detection of potential security disturbances. However, several challenges were identified, including limited personnel, lack of community participation, and insufficient facilities and infrastructure to support the program.